Detailed investigation of TLM contact resistance measurements on crystalline silicon solar cells. (15th July 2017) - Guo, Siyu; Gregory, Geoffrey; Gabor, Andrew M.; Schoenfeld, Winston V.; Davis, Kristopher O.
Highlights: Various problems about TLM for c-Si solar cells are studied for the first time. Influence from strip width on TLM measurement for c-Si solar cell is investigated. Influence from edge shunting and unprobed fingers on TLM measurement are studied. Effective correction methods are proposed for where problem happens. Measurement error for a 30 mm sample is reduced from 94.5% to 4.5% with correction. Abstract: The transmission line method (TLM) is often used in characterizing the contact resistance of c-Si solar cells by cutting cells into strips parallel to the busbars. When applying this method to industrial solar cells, we found various problems that have not been sufficiently explained in prior work. In this paper, we investigate different factors that influence the accuracy of this measurement, using both simulation and experimental methods. The following factors are shown to influence the extracted contact resistivity and are investigated in this work: (1) strip width; (2) edge shunting; (3) current flow through the intermediate unprobed fingers; (4) non-uniform contact resistance; and (5) non-uniform sheet resistance. In cases where the contact resistivity values determined from the TLM measurements and simulations were found to be inaccurate, we introduce correction procedures and measurement guidelines that reduce error. For example, when strip width is a factor, the measurement error of a 30 mm sample is reduced from 95.5% to 4.5% using a correction procedure validated by simulation. Furthermore, the methods are also shown to be very effective when applied to industrial solar cells. TLM measurements have an important role to play in both cell R&D and factory quality control, and this work can serve as a guide towards more accurate contact resistivity measurements.